Supervisor, Colleague, or Assistant: General Surgery Resident Perceptions of Advanced Practitioners. Issue 2 (February 2018) - Clark, Clancy J.; Hildreth, Amy; Migaly, John; Sieren, Leah; Carter, Jeffrey; Stewart, John H.
Integration of advanced practitioners (APs) into academic medical centers can improve processes of care and decrease physician workload but may adversely impact general surgery residency training. The aim of the present study was to characterize general surgery resident perceptions of APs and their impact on resident training. We conducted an institutional review board–approved survey covering five topic areas: knowledge of AP training, interaction with APs, scope-of-practice of APs, role of APs in the health-care team, and impact of APs on physician training. The survey was administered to general surgery residents at six large academic medical centers. One hundred eighteen general surgery residents completed the survey. The majority (43.6%) of respondents were junior residents. All respondents had interactions with APs with 90.7 per cent having worked directly with an AP in the last month. Residents reported minimal formal educational involvement by APs with 6.8 per cent reporting participation in didactics and 22.2 per cent teaching operative techniques. Almost half (44.1%) of the respondents reported that APs played an important role in their education, and 42.4 per cent of respondents disagreed or strongly disagreed that the role of the AP is well defined in their hospital. Today's general surgery residents work closely with APs who seem to positively impact resident education. Although residents perceive significant benefit with integration of APs, well-defined roles are lacking.